Laser-induced texturing: A sustainable approach to self-cleaning mechanisms in solar panel - Rahool Rai; Mahadzir Ishak; Aiman Bin Mohd Halil; M.M. Quazi; Sudhakar Kumarasamy (Cleaner Engineering and Technology)
This review paper discusses the application of laser surface texturing as a novel approach for inducing self-cleaning properties in solar panels, with a particular focus on glass surfaces. Despite the limitation in literature on this specific topic, this study integrates available information to provide a comprehensive overview. Apparently, the challenges posed by sunlight reflection and dust accumulation on photovoltaic panels are addressed through the application of anti-reflective and self-cleaning coatings. But coatings consists of hazardous chemicals such as: TiO2, SiO2, ZnO, Si3N4,MgF2 and ZrO2. Therefore, the focus here shifts towards the modern use of laser technology for surface modification. The literature shows involvement of optimization of laser processing parameters, including laser power, scanning speed, repetition rate and their interdependent relation, to achieve super-hydrophobic surfaces. Therefore, emphasis on the significance of understanding the effects of laser parameters on the resulting surface characteristics, such as water contact angle, self-cleaning efficiency, and opacity of the glass is discussed. Several studies conducted for metals show the effectiveness of laser-textured surfaces in mitigating dust accumulation. The discussion also touches upon the challenges and advantages of laser-based texturing, due to cost-effectiveness, precision, and speed. Specifically addressing laser surface texturing for solar self-cleaning applications. This research gathers current information to highlight the remarkable potential of laser technology in improving the performance and longevity of solar panels by instilling self-cleaning properties.